Membatik sebagai Media Edukasi Berbasis Kearifan Lokal guna Pewarisan Budaya di Museum Batik Pekalongan - Muhammad Irfan Setiawan; Tutik Wijayanti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Batik is an ancestral cultural heritage asset that represents the diversity of the Indonesian nation. The Pekalongan Batik Museum is a tangible manifestation of cultural preservation in the city of Pekalongan. The Pekalongan Batik Museum functions as a center for the preservation and education of batik culture, as evidenced by the acquisition of a certificate from UNESCO for the best batik practices . This study aims to describe the implementation of batik activities as an educational medium based on local wisdom at the Pekalongan Batik Museum. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research informants consisted of the Head of the Batik Museum, workshop staff, conservation staff, and museum visitors. The results of the study show that batik activities at the Pekalongan Batik Museum not only function as an art activity, but also as a learning medium that strengthens character, introduces cultural values, and fosters a sense of love for local culture. The museum applies adaptive educational methods according to the age of visitors, as well as providing creative space for participants to explore batik motifs. This educational process makes for an active, contextual, and meaningful learning experience. So that museums are not only a place for preserving artifacts, but also as a dynamic cultural heritage agent. This finding has the prospect of being implemented in other educational institutions and educational tourism to strengthen the nation's cultural identity.